OP0179 Different Levels of Moderate Disease in Rheumatoid Arthritis (RA) are Associated with Varying Risk for Joint Destruction and Failure. Time to Update Das Cut-Offs for Biologic Dmard Use?. (9th June 2015) - Nikiphorou, E.; Carpenter, L.; Norton, S.; Kiely, P.; Dixey, J.; Young, A.
Abstract : Background: Sustained high disease activity in RA is known to result in worse outcomes. However, many patients remain in moderate disease activity states, yet their outcomes, are less well studied. Objectives: To examine orthopaedic surgery as a surrogate marker of joint failure in patients who remain at different moderate disease activity levels in the first 5 years from disease-onset. Methods: The Early RA Study (ERAS, n=1465, 1986-1999) and the Early RA Network (ERAN, n=1236, 2002-2012) collected standard clinical, radiological and laboratory measures yearly for a maximum (median) 25 (10) and 10 (3) years respectively. Clinical databases were validated with national sources: the National Joint Registry, Hospital Episode Statistics & National Death Register. Treatment regimens followed guidelines of the era, mainly conventional DMARDs & latterly biologics. Joint interventions were categorized into major (large joint replacements), intermediate (mainly synovectomies & arthroplasties of wrist/hand, hind/forefoot) or minor (mainly soft tissue). Mean DAS28 was calculated for each patient from year1 (after treatment-onset) to 5 and categorized into either remission [RemDAS ≤2.6], low [LowDAS >2.6 -3.2], low moderate [LowModDAS= >3.2-4.19], high moderate [HighModDAS 4.2-5.1] or high DAS [HighDAS >5.1]. Results: A total of 2044 (76%) patients had at least two DAS28 recorded between year 1-5: 21% in RemDAS, 15% in LowDAS, 26% in LowModDAS, 21% in HighModDAS, 18% in HighDAS categories. The table shows that on moving from remission through to low/moderate/high states there was a progressive worsening in baseline clinical & laboratory variables. In multivariate Cox regression models controlling for age at disease onset, gender, recruitment year, symptom duration, baseline rheumatoid factor, BMI, HAQ, erosions and Haemoglobin, HighModDAS (HR 1.80, 95%CI 1.05-3.11, p=0.034) and HighDAS (HR 2.59, 95%CI 1.49-4.52, p=0.001) predicted higher risk for intermediate surgery, unlike LowModDAS or LowDAS categories. In the case of major joint surgery, LowModDAS (HR 2.07, 95%CI 1.28-3.33), HighModDAS (HR 2.16, 95%CI 1.32-3.52) and HighDAS (HR 2.48, 95%CI 1.50-4.11) all predicted an increasing risk (p<0.005). Conclusions: Patients who remain in low or high moderate disease activity levels in the first 5 years of disease, despite conventional DMARD therapy, have similar risks for joint failure and surgery as those with persistently high DAS. This is highly relevant in health systems where restrictions exist in the use of biologic DMARDs, which are based on DAS cut-offs and exclude moderate RA. Disclosure of Interest: None declared